Rational Design of P450 aMOx for Improving Anti-Markovnikov Selectivity Based on the “Butterfly” Model - Pan, Yue; Bao, Jinxiao; Zhang, Xingyi; Ni, Hui; Zhao, Yue; Zhi, Fengdong; Fang, Bohuan; He, Xiao; Zhang, John Z. H.; Zhang, Lujia (Frontiers in Molecular Biosciences, 2022)
Aromatic aldehydes are important industrial raw materials, mainly synthesized by anti-Markovnikov (AM) oxidation of corresponding aromatic olefins. The AM product selectivity still remains a big challenge. P450 aMOx is the first reported enzyme that could catalyze anti-Markovnikov (AM) oxidation of aromatic olefins. Here we report a rational design strategy based on ‘butterfly’ model of the active site of P450 aMOx. Constrained molecular dynamic simulations and key binding residuals analysis combined with experimental alanine scan were applied. As a result, the mutant A275G realized high AM selectivity of >99%. The result also proved that the ‘butterfly’ model is an effective design strategy for enzyme.